A fatal septic shock caused by Capnocytophaga gingivalis potentially associated with COVID‐19: A case report - Dai Miyazaki; Chika Kunishige; Shigeru Sano; Kahoru Urakawa; Kana Okamoto; Naomi Morishita; Kentaro Iwata (Acute Medicine & Surgery)
Abstract Background Capnocytophaga spp. is associated with fulminant sepsis, particularly in those with immunosuppression. We here report a rare case of fatal fulminant septic shock caused by C. gingivalis, concurrent with COVID‐19. Case Presentation A Japanese woman developed septic shock, which led to her death. Polymerase chain reaction (PCR) testing of the respiratory specimen was positive for SARS‐CoV‐2, and a CT scan of the chests revealed bilateral ground glass opacities. The blood cultures identified C. gingivalis. The patient had rheumatoid arthritis and was taking prednisone orally. There were no splenic abnormalities shown on the CT scan. Conclusion A rare case of fulminant septic shock caused by C. gingivalis, together with COVID‐19 was identified. The precise pathogenesis of this combination, together with the best treatment option should be sought by further studies.